ANALISA PENGARUH CITRA MEREK, HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR YAMAHA NMAX DI KOTA SURAKARTA - Saputro, Endro Aryo; Widiastuti, Erni (Surakarta Management Journal, 2020)
The purpose of this study was to determine: 1) the influence of brand image on purchasing decisions of Yamaha NMAX motorcycles in Surakarta, 2) the effect of prices on purchasing decisions of Yamaha NMAX motorcycles in Surakarta, 3) the effect of product quality on purchasing decisions of Yamaha motorcycles NMAX in Surakarta City, 4) Simultaneous influence of brand image, price, product quality on purchasing decisions of Yamaha NMAX motorcycle in Surakarta City. This research is a quantitative descriptive study whose conclusions are obtained based on the results of statistical analysis with the object of research are Yamaha NMAX motorcycle users in the city of Surakarta. The sample is 100 respondents, where the sampling technique is accidental sampling technique.The instrument used with the questionnaire and data analysis technique used was multiple linear regression analysis, t test, F test, R2 test. Regression analysis results obtained by the regression equation: Y = -10,906 + 0,395X1 + 0,366 X2+ 0,410 X3, which means that purchasing decisions of Yamaha NMAX motorcycles in Surakarta City are influenced by brand image, price and product quality. Based on the analysis and discussion it can be concluded that: 1) brand image significantly influences the purchasing decision of NMAX motorcycles in Surakarta. (2) the price significantly affects the purchase decision of NMAX motorcycles in the city of Surakarta.  (3) product quality significantly influences the purchasing decision of NMAX motorcycles in Surakarta. (4) brand image, price, and product quality simultaneously significantly influence NMAX motorcycle purchasing decisions in Surakarta. Judging from the coefficient, the brand image, price, and product quality were determined to influence the purchasing decision of NMAX motorcycles in Surakarta by 82.6%, while the remaining 17.4% was influenced by other variables outside this study.